Gestational Perfluorooctanoic Acid Exposure Inhibits Placental Development by Dysregulation of Labyrinth Vessels and uNK Cells and Apoptosis in Mice - Jiang, Wenyu; Deng, Yu; Song, Zifan; Xie, Yajuan; Gong, Lixin; Chen, Yilu; Kuang, Haibin (Frontiers in Physiology, 2020)
Perfluorooctanoic acid (PFOA) is a widely used perfluorinated compound and known to cause developmental toxicity which includes the increase of resorbed embryo, decrease of fetal survival and fetal growth retardation. Nevertheless, whether it is associated with alteration of placental development remains unknown. Pregnant mice were gavaged with 0, 2.5, 5, 10 mg PFOA /kg/day from pregnancy day (PD) 1 to PD 13. Results showed that PFOA exposure markedly decreased the placental weight and caused interstitial edema of placenta. Laminin staining indicated that blood sinusoids area was shrunken in placenta of PFOA-exposed mice. Furthermore, PFOA treatment significantly reduced numbers of uNK cells. Western blot analysis revealed that levels of Bax and cleaved-caspase 3 proteins were markedly up-regulated in PFOA-treated groups. In addition, TEM examination showed that PFOA treatment caused rupture of nuclear membrane and nuclear pyknosis and fragmentation. Thus, our results suggested that gestational PFOA exposure significantly inhibited development of early placenta through shrinkage of labyrinth vessels and downregulation of uNK cells and apoptosis induction, which may result in adverse gestational outcomes.